2011
DOI: 10.1177/0883073811423974
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Delays in Children With Neurofibromatosis Type 1

Abstract: It is well documented that children with neurofibromatosis type 1 are at high risk for a variety of cognitive and learning deficits. The current study investigated the use of a developmental screening tool, the Parents' Evaluation of Developmental Status: Developmental Milestones, as an accurate, reliable, and efficient indicator of developmental delays. Sixty-eight percent of children with neurofibromatosis type 1 were found to have a developmental delay in at least 1 of the 8 areas tested by the Parents' Eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 19 publications
3
33
0
Order By: Relevance
“…This condition should be suspected in children with hypotonia and multiple (greater than 6) café au lait spots. 27 Children with known or suspected genetic disorders may benefit from genetic consultation and genetic counseling for the family.…”
Section: Neuromotor Examinationmentioning
confidence: 99%
“…This condition should be suspected in children with hypotonia and multiple (greater than 6) café au lait spots. 27 Children with known or suspected genetic disorders may benefit from genetic consultation and genetic counseling for the family.…”
Section: Neuromotor Examinationmentioning
confidence: 99%
“…5 There is an emerging body of evidence demonstrating motor impairment as a common feature of NF1 in childhood. 4,6,7 Early research in this area documented problems with manual dexterity, balance, and ball skills, with 32% of children exhibiting severe impairment of coordination skills. 8 More recently, Johnson et al compared children with NF1 with normative data on the Bruininks Oseretsky Test of Motor Proficiency, 2nd Edition (BOT-2).…”
Section: Discussionmentioning
confidence: 99%
“…4 Associations have also been reported between fine motor, maths/premaths skills, and focal areas of hyperintensity on T2-weighted cerebral images. 7 Reduced motor competency may contribute to a range of poor outcomes for children with NF1. Gross motor skill impairments, for example, have been shown to predict a range of social, emotional, behavioural, and academic problems in children with developmental coordination disorder, all of which are common features of the NF1 phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ras-MAPK pathway dysregulation is also implicated in autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD), of which augmented prevalence rates occur in NF1 populations (Garg et al, 2013;Walsh et al, 2013). Co-occurring gross and/or fine motor problems are common in NF1 (Soucy, Gao, Gutmann, & Dunn, 2012) as well as in ADHD (McLeod, Langevin, Goodyear, & Dewey, 2014) and ASD (Gustafsson et al, 2014). Fine motor problems in children with NF1, such as writing difficulties may lead to significant difficulties in daily life functioning and academic achievement (Krab et al, 2011) and are found to significantly coincide with impaired visual-motor performance as measured with the copy subtest of the Beery Buktenica developmental test of visual motor integration (Beery VMI) (Gilboa, Josman, Fattal-Valevski, Toledano-Alhadef, & Rosenblum, 2010;Krab et al, 2011).…”
Section: Introductionmentioning
confidence: 99%